Decreased retinal sensitivity after internal limiting membrane peeling for macular hole surgery - Tadayoni, Ramin; Svorenova, Ivana; Erginay, Ali; Gaudric, Alain; Massin, Pascale (British journal of ophthalmology, 2012)
Aims To compare the retinal sensitivity and frequency of microscotomas found by spectral domain optical coherence tomography (SD-OCT) combined with scanning laser ophthalmoscopy (SLO) microperimetry after idiopathic macular hole closure, in eyes that underwent internal limiting membrane (ILM) peeling and eyes that did not. Methods This was a retrospective, non-randomised, comparative study. Combined SD-OCT and SLO microperimetry was performed in 16 consecutive eyes after closure of an idiopathic macular hole. A customised microperimetry pattern with 29 measurement points was used. The ILM was peeled in 8/16 eyes. The main outcome measure was mean retinal sensitivity. Results Mean retinal sensitivity (in dB) was lower after peeling: 9.80±2.35 dB with peeling versus 13.19±2.92 without (p=0.0209). Postoperative microscotomas were significantly more frequent after ILM peeling: 11.3±6.6 points with retinal sensitivity below 10 dB in eyes that underwent peeling versus 2.9±4.6 in those that did not (p=0.0093). Conclusions These results suggest that ILM peeling may reduce retinal sensitivity, and significantly increase the incidence of microscotomas. Until a prospective trial confirming or not these results, it seems justified to avoid peeling the ILM when its potential benefit seems minor or unproved, and when peeling is carried out, to limit the surface peeled to the bare minimum.